Upaya Orang Tua terhadap Perilaku Menyimpang di Kalangan Remaja di Desa Kendayakan Kabupaten Serang (International Forum of Researchers and Lecturers, 2025)
Adolescence is often regarded as a vulnerable and critical period, marked by the transition from childhood to adulthood. In today’s context, this phase is frequently described as a time of crisis due to the lack of proper guidance during personality formation. Teenagers require support and direction, particularly from their parents, to help navigate this stage. The family plays a crucial role in shaping behavior and is considered the primary institution responsible for preventing and addressing juvenile delinquency. A harmonious family life often reflects in the child’s behavior and interaction with the environment. When parents are actively involved in guiding and mentoring their children, adolescents are more likely to become positive role models. Deviant behavior among teenagers has become a pressing issue, especially considering that the youth are regarded as future assets for the nation, state, and religion. This study aims to: (1) Identify the factors that cause deviant behavior among teenagers in Kendayakan Village, Serang District; and (2) Explore the efforts made by parents to address such behavior. A qualitative research method with a case study approach was employed. Data were collected using three techniques: observation, interviews, and documentation. The analysis was carried out using qualitative descriptive methods. The findings reveal that deviant behavior among teenagers in Kendayakan Village is influenced by two main factors: (a) environmental factors, such as peer influence and lack of positive role models, and (b) individual factors, including emotional instability and lack of self-control. Meanwhile, the efforts made by parents include providing supervision, instilling discipline, offering advice and religious education, and collaborating with schools and community leaders. These efforts highlight the critical role of parental intervention in preventing and addressing adolescent deviance.